Peningkatan Prestasi Belajar Geografi menggunakan Metode Pembelajaran Student Facilitator And Explaining pada Siswa Kelas VII E UPTD SMPN 4 Pare Kediri - Ronggowulan (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
This study examines the improvement of the learning performance of geography subjects with the material ' describing the face of the earth, the process of forming & impact on life ' using student facilitator and explaining learning methods in class VII E UPTD SMPN 4 Pare Kediri. Using the classroom Action Research approach, the study showed that the use of learning methods for student facilitators and explaining:: (1) was effective and successful in improving student learning performance. This is evidenced by the increase in the average student learning outcomes from before the study of 77.27 to 86.66 (increased 9.39). As for the guidance of learning students before the Prosentasenya research is 22.73% (12 students) increased after research conducted to 100% (40 students). It appears that the classical distance increased by 77.27%; (2) effective and successful in enhancing students ' active learning. This is evidenced by the increase of student activity from each of the biggest enhancement indicators seen in the activity of active students when the group discussion from before the research was 22.73% to 100% (increase by 77.27%). To streamline the use of learning methods facilitator and explaining students need a teacher's clarity in realizing the level of student understanding and saturation. So that when students have been saturated with materials and students are less able to understand well, teachers should be able to provide strengthening understanding of the material.